English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I keep getting 2x^2 - xy -2xy +y^2 +2xz - yz

answer is 2x^2 - 3xy +2xz + y^2 - yz

2006-12-21 07:19:16 · 4 answers · asked by grem 3 in Computers & Internet Internet

4 answers

2x * x = 2x^2
2x * -y = -2xy
2x * z = 2xz

-y * x = -xy
-y * -y = y^2
-y * z = -yz

Summation of terms = 2x^2 -3xy +2xz +y^2 -yz


Slow down and write out all the steps - I know it's time consuming, but it will help!

2006-12-21 07:24:23 · answer #1 · answered by Rebecca H 2 · 0 0

Have to make sure you use foil, but match every term.

2x and x, 2x and y, 2x and z etc
To begin:

2x^2 - 2xy + 2xz - xy + y^2 - yz simplify;
2x^2 - 3xy + 2xz + y^2 - yz

Shazaam.

2006-12-21 07:22:58 · answer #2 · answered by p_rutherford2003 5 · 0 0

Don't worry YOU are halfway right!
The only problem here is simplifying what you ended up with...You need to "Add"
the -xy and the -2xy to create "-3xy".....*wink*

Cuz I take you already know how to start this problem right?
*(2x-y) (x-y+z)

2x(x)=2x(squared)
2x(-y)=-2xy
2x(z)= 2xz

AND
y (x)=yx
y(y)= y(squared)
y(z)= yz

So... here's the answer you got
2x (squared) -2xy+2xz-xy+y(squared)-yz

Simplify:
2x (squared) -3xy+2xz+y(squared) -yz
(xy is paired with -2xy...but y(squared) and -yz aren't pair with nothing else..*wink*)

Happy Holidays! =)

2006-12-21 07:40:01 · answer #3 · answered by Anonymous · 0 0

For the first difficulty, use F * O * I * L. (First, Outer, inner, very last) (x + 3) (x + a million) = x^2 + 3x +1x + 3 = x^2 + 4x + 3 ------------ 2d difficulty: (7 + r)^2 is the same as: (7 + r) (7 + r) or (r + 7) (r + 7) (use F * O * I * L again) = r^2 + 7r + 7r + 40 9 = r^2 +14r + 40 9 -------------- 0.33 difficulty: (6s - 7)(7s^2 - s + 4) Use the distributive resources of multiplication. Multiply 6s by skill of the 2d set of parenthesis: 6s (7s^2 - s + 4) = 42s^3 - 6s^2 + 24s Multiply the -7 by skill of the 2d set of parenthesis: -7 (7s^2 - s + 4) = -49s^2 +7s - 28 upload your consequences mutually and combine like words: = 42s^3 - 6s^2 + 24s - 49s^2 +7s - 28 = 42s^3 - 6s^2 - 49s^2 +7s + 24s - 28 = 42s^3 - 55s^2 + 31s - 28 <== answer sturdy success on your study, ~ Mitch ~

2016-11-28 02:30:19 · answer #4 · answered by ? 4 · 0 0

fedest.com, questions and answers